Energy sustainable greenhouse crop cultivation using photovoltaic technologies. (July 2019) - Yano, Akira; Cossu, Marco
Abstract: The sustainability of energy and food supplies has come to represent a major concern throughout the world today. Greenhouse cultivation, an intensive food-production system, contributes fresh vegetables and fruits to the world food supply. Greenhouse crop yields and quality can be improved by microclimate controls powered by fuels and grid electricity inputs. Therefore, producing abundant and quality crops with improved energy efficiency has been pursued as a challenge to be addressed by researchers and practitioners. Although application of photovoltaics (PV) to greenhouses can reduce fuel and grid electricity consumption, PV inherently conflicts with cultivation because both photosynthesis and PV depend on sunlight availability. Various contrivances have been explored to enhance the compatibility of cultivation and PV power generation. This review describes important aspects of greenhouse cultivation, electricity demand in greenhouses, state-of-the-art of greenhouse PV systems, and PV shading effects on plants. Finally, prospects for energy-sustainable greenhouse PV technologies are presented. Highlights: Electricity demand in worldwide greenhouses is presented. Solar cells are applicable to greenhouses in various ways. Greenhouse-installed photovoltaics can generate large amounts of electricity. Photovoltaic panel shading affects plants below the panels.